MALAYSIAN LICHENS—III* - P. GROBNHART (REINWARDTIA, 1951)
Amongst the lichens sent by the late Mr C. C. Schroter at Tjibodas (West Java),a peculiar blue-grey species drew my attention.At first sight I intended to assign it provisionally to Collemaceae indeterminatae,but on closer examination I doubted whether it was really a species of Collemaceae.Therefore.I examined it more carefully, with the following result.The granular thallus grows in smaller to larger patches over mosses,lichens, and detritus on bark.Soredia and isidia are absent and the thallus is not surrounded by a dark hypothalline line.The granular appearance of the thallus is caused by the relatively large gonidia, which belong to Stygonemataceae.The yellowish green cells are rounded,angular to semilunate, 8—12µ, wide and 10—15 µ long; one or more of them are enclosed within a gelatinous,colourless to pale citrine sheeth 4—6µ thick. These clusters of gonidia are held together by the thalline hyphae constituting in this way a homoiomeric thallus.There is some resemblance with the thallus of Moriolaceae but in this family the gonidia are totally surrounded with a network of short hyphae lying close together.In the thallus of Cyanoporina, as I call this new lichen, such a network does not exist.The hyphae lie irregularly around the gonidia and cover them but partly. These gonidial hyphae are 2—3µ thick and possess very short cells. The thalline hyphae are 3 µ,thick, with inconspicuous lumen.Even with the aid of a dissecting microscope the perithecia are almost invisible.Most of them are covered by the granules of the thallus.Yet the thallus is abundantly fruiting and in sections perithecia are always present. They are globose, 110—130µ in diameter, pale fulvescent to yellowish, with a pseudoparenchymatic wall 10—12 µ thick, composed of densely interwoven hyphae. I could, not discover a pore.The paraphyses are diffluent and only fragments were found.